Strengthening Nationalism through the Implantation of Religious Values and Environmental Cleanliness Among Children of SB Rawang - Rizki Maulana; Mohamad Ziad Pilomonu; Rahmat Dunggio; Harun Joko Prayitno; Djumadi Djumadi; Minsih Minsih; Ika Kusuma Wardani; Rakhma Widya Dharojah (International Conference on Education for All, 2023)
The VIth International Partnership Education Real Work Lecture (KKN-DIK KI) which was held in Malaysia, Rawang Guidance Studio, village road 4/3, Bandar Country Homes, Rawang city for 4 weeks starting on March 13 2023 to April 8 2023 This studio was chosen as a place for KKN because it has students who are Indonesian children. KKN begins with a SB analysis process to find out what is needed to become the main reference for the activity program during the KKN. Programs are designed sequentially and according to SB's needs, starting from member meetings to determining program implementation schedules and meetings with studio supervisors. The implementation of the KKN activity program is carried out in a balanced and gradual manner, starting with planning, implementation and evaluation at the end of each program. The results of the entire KKN program include in the field of education, SB children can read the alphabet and count, in the field of culture they can learn several Indonesian national songs and regional songs, in the field of nationalism they can learn the names of heroes and provinces in Indonesia, in the field of religion they can add memorizing short suras, and in the health sector can foster a sense of concern for the cleanliness of the surrounding environment